Temperature-dependent vibrational spectroscopic studies of pure and gold nanoparticles dispersed 4-n-Hexyloxy-4'-cyanobiphenyls. Issue 9 (15th July 2018) - Mishra, Ramanuj; Bhattacharjee, Ayon; Bhattacharjee, Debanjan; Singh, Keisham Nanao; Gogoi, Binod; Alapati, Parameswara Rao
ABSTRACT: Raman spectra of pure and 2 wt.% gold nanoparticles (GNPs) dispersed liquid crystalline compound 4-n-Hexyloxy-4ʹ- cyanobiphenyls (6OCB) has been recorded as a function of temperature from room temperature (solid crystal) to 80°C (isotropic liquid) in the spectral region of 500–2500 cm −1 . The variation of Raman spectral parameters (peak positions and line width) with temperature is used to explain the changes in molecular alignment and its effect on inter-/intra-molecular interactions at crystal-Nematic (K-N) transition. To understand the change in molecular structure during phase transition and on account of dispersion of gold nanoparticles in pure liquid crystal more precisely, two spectral regions 1000–1500 cm −1 and 1500–2400 cm −1 have been selected separately. From the detailed study, it is concluded that increased orientational/vibrational freedom of the molecules as well as delocalisation of electron clouds results in the spectral anomalies at K-N transition. The geometrical structure of 6OCB was optimised using density functional theory (DFT) and theoretical Raman spectra have been obtained for comparison with experimental spectra. The tentative assignment of vibrational modes observed in our region of study was calculated based on potential energy distribution (PED) using vibrational energy distribution analysis (VEDA) calculation. Graphical Abstract: